Предмет: Алгебра,
автор: dka2010
3tg(pi*x)+5ctg(pi*x)+8=0
Ответы
Автор ответа:
0
Решение:
3tg(pi*x)+5ctg(pi*x)+8=0
3tg(pi*x)+5*1/tg(pi*x)+8=0
tg(pi*x)=t
3t^2+8t+5=0
t=(-4+-sqrt(16-15))/3
t1=(-4+1)/3=-1
t2=-5/3
tg(pi*x)=-1
pi*x=-pi/4+pi*k
x=-1/4+k
tg(pi*x)=-5/3
x=-1/pi*arctg(5/3)+k.
3tg(pi*x)+5ctg(pi*x)+8=0
3tg(pi*x)+5*1/tg(pi*x)+8=0
tg(pi*x)=t
3t^2+8t+5=0
t=(-4+-sqrt(16-15))/3
t1=(-4+1)/3=-1
t2=-5/3
tg(pi*x)=-1
pi*x=-pi/4+pi*k
x=-1/4+k
tg(pi*x)=-5/3
x=-1/pi*arctg(5/3)+k.
Похожие вопросы
Предмет: Математика,
автор: Osovska
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: narsudinkar
Предмет: Математика,
автор: Natasha00793
Предмет: Химия,
автор: Ru123tc